Definition and taxonomic revision of the karst-associated Odorrana lipuensis group (Anura, Ranidae), with a new species from Guangdong, China - Han-Ming Song; Shuo Qi; Hao-Tian Wang; Yue-Ning Gong; Yang Liu; Ying-Yong Wang (Zoosystematics and Evolution)
While taxonomy of the odorous frog genus Odorrana has made considerable progress recently, far less attention was given to those newly-described karst-associated species. In this study, the taxonomic status of Odorrana lipuensis group, species living in karst environments, was revisited. Combining the scrutiny of previous literature, molecular analyses using two mitochondrial DNA fragments (i.e. 16S rRNA and CO1) and morphological analyses including a series of additional specimens, we defined the O. lipuensis group and revised the taxonomic accounts of recognised species. Based on these data, we described a new species, O. calciphila sp. nov. from the karst regions in northern Guangdong, China. Apart from this new species, the O. lipuensis group currently contains three other species distributed in southern China and northern Vietnam, namely O. concelata, O. liboensis and O. lipuensis. Morphological comparisons between this group and other congeners, together with a dichotomous identification key for each species within this group, were also presented. Finally, the known distribution, implications of morphological distinctiveness, ecological and evolutionary significances and existing taxonomic issues of these species were also discussed.